Analisis Metode Drill dalam Pembelajaran Seni Budaya Siswa Kelas II SDN Perumnas 1 - Hani Hanifah; Sumiyani Sumiyani; Arry Patriasurya Azhar (Journal on Education, 2023)
This study discusses the drill method in learning cultural arts in schools. This study aims to describe the results of the Drill method in learning art and culture with simple rhythm patterns. This research is a descriptive qualitative research by taking data at SDN Perumnas 1. with the subject and object of research to Class II Teachers, Class II students, and also Parents of Class II students. Methods of data collection using observation, interviews, and documentation. Data analysis was collected by collecting data, reducing data, presenting data, and drawing conclusions. The results obtained are the drill method in learning art and culture of simple rhythm pattern class II SDN Perumnas 1 can be said to be good because SDN Perumnas 1 has implemented the drill method since the beginning of learning. But there are some students who do not understand the lesson. when given a question the answer is not right. From the explanation of the second grade teacher, students have received cultural arts learning by applying the drill method well and almost completely learning art and culture is achieved.